2018
DOI: 10.1002/cnr2.1134
|View full text |Cite
|
Sign up to set email alerts
|

Working poor and working nonpoor cancer survivors: Work‐related and employment disparities

Abstract: Background Many cancer survivors face challenges remaining at work during treatment or returning to work posttreatment. Workplace supports can ease the strain associated with managing the cancer‐work interface. Limited research has examined the employment experiences of low‐wage earning survivors, who are less likely to have access to workplace supports, overlooking a factor that may influence survivors' employment outcomes. Aims This study assessed differences in employment experiences between working poor (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Demographic factors such as age, gender, and education level influence the ability to continue work after cancer [ 16 19 ]. In Norway, fewer women than men are employed 5 years after cancer [ 20 ] and reducing working hours after cancer are more common among women than men [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demographic factors such as age, gender, and education level influence the ability to continue work after cancer [ 16 19 ]. In Norway, fewer women than men are employed 5 years after cancer [ 20 ] and reducing working hours after cancer are more common among women than men [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Hispanic or Latinx individuals are more likely than both White and Black individuals to work in construction and maintenance (38). These employment categories may offer less flexible schedules, hourly versus salaried payment arrangements, and less opportunity for remote work (23,39,40), all of which have been shown to be important accommodations to individuals undergoing cancer treatment (34,35,41). Third, access to more generous benefit policies, including disability insurance, paid time off, and employer-sponsored health insurance, is more common among individuals in higher earning jobs and more common among White workers versus workers of color in the United States (21,22,42).…”
Section: Discussionmentioning
confidence: 99%
“…These groups include cancer survivors with lower income, low level of education, being from a minoritized ethnic background and/or being unemployed, work disabled or in precarious employment at the time of diagnosis. 17 , 20 , 24–26 …”
Section: Factors Related To Adverse Work Outcomesmentioning
confidence: 99%
“…Regarding physical fatigue, previous research found that low physical functioning is associated with work outcomes. 24 Two recent reviews further indicated that cancer survivors can experience adverse work outcomes due to various cognitive deficits, such as a loss of concentration, memory and executive functioning. 31 , 32 Finally, emotional fatigue including a lack of motivation 18 and experiencing work stress were also found to be related to adverse work outcomes.…”
Section: Factors Related To Adverse Work Outcomesmentioning
confidence: 99%